Survey Tingkat Gemar Membaca pada Siswa di SDN Kalianget Barat II dalam Era Digitalisasi - Ubaidillah, Ahmad Ulya; Hidayatullah, Ahmad Syarif; Putri, Intan Aprilia; Mas’odi, Mas’odi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the level of reading interest in students at SDN Kalianget Barat II and the factors that can influence it. By using a qualitative descriptive method with data collection through interviews and observations at SDN Kalianget Barat II. The survey results show that most students at SDN Kalianget Barat II have a low level of reading interest. With the majority of students preferring to use gadgets to play games. So that this can be a challenge and a problem that must be faced by students and teachers in the learning process. There are many factors that influence this, namely lack of family support, lack of motivation and environmental factors. This study is expected to be a reference for schools and the government to increase students' reading interest in the digital era.